Revolutions in the Atlantic world : a comparative history - Klooster, Wim. (New York : New York University Press, 2009)
Reveals several central themes in the field of Atlantic history, from the concept of European empire to slavery and Diaspora
1. Introduction: Empires at War -- 2. Civil War in the British Empire: The American Revolution -- 3. The War on Privilege and Dissension: The French Revolution -- 4. From Prize Colony to Black Independence: The Revolution in Haiti -- 5. Multiple Routes to Sovereignty: The Spanish America Revolutions -- 6. The Revolutions Compared: Causes, Patterns, Legacies.
Includes bibliographical references and index.
ENH
Trim Education
Keywords: Revolutions -- America -- History -- 18th century; Revolutions -- America -- History -- 19th century; English language; Revolutions -- Cross-cultural studies; Sovereignty -- Cross-cultural studies; United States -- History -- Revolution, 1775-1783.; France -- History -- Revolution, 1789-1799.; Haiti -- History -- Revolution, 1791-1804.; Latin America -- History -- Wars of Independence, 1806-1830.